A new geomagnetic observatory at Livingston Island (South Shetland Islands): Implications for future regional magnetic surveys - Torta, Joan Miquel; Gaya-Piqué, Lluís; Solé, J. Germán; Blanco-Montenegro, Isabel; García García, Alicia (Istituto Nazionale di Geofisica, 1999)
11 pages, 6 figures. A permanent geomagnetic observatory is always the ideal reference station for monitoring geomagnetic activity during airborne, marine or ground magnetic surveying, especially in Antarctica, where logistic difficulties are an important factor even for the deployment of temporary base stations. The utility of the magnetic observatory records for the correct reduction of the survey data is reinforced if both their spatial homogeneity and their particular anomaly biases are assessed. This, combined with data from the magnetic surveys themselves, can yield information on the crustal contribution to the Earth's magnetic field from a remote and poorly understood region. With these objectives in mind, we present a new geomagnetic observatory in the South Shetland Islands, where (because of the complex regional tectonic characteristics) magnetic surveys on one or another structure are conducted from time to time. An evaluation of the observatory representativeness and a look at the crustal magnetic anomaly ambience are also given. This work is part of the Research Project ANT95-0994-C03, supported by the Spanish Comisión Interministerial de Ciencia y Tecnología. Peer reviewed